Infant Growth after Preterm Birth and Mental Health in Young Adulthood - Sammallahti, Sara (PLoS One, 2015)
OBJECTIVES: Faster growth after preterm birth benefits long-term cognitive functioning. Whether these benefits extend to mental health remains largely unknown. We examined if faster growth in infancy is associated with better self-reported mental health in young adults born preterm at very low birth weight (VLBW) (<1500g). STUDY DESIGN: As young adults, participants of the Helsinki Study of Very Low Birth Weight Adults self-reported symptoms of depression and attention deficit/hyperactivity disorder (ADHD) (n = 157) and other psychiatric problems (n = 104). As main predictors of mental health outcomes in linear regression models, we used infant weight, length, and head circumference at birth, term, and 12 months of corrected age, and growth between these time points. Growth data were collected from records and measures at term and at 12 months of corrected age were interpolated. Additionally, we examined the moderating effects of intrauterine growth restriction. RESULTS: Size at birth, term, or 12 months of corrected age, or growth between these time points were not associated with mental health outcomes (p-values >0.05). Intrauterine growth restriction did not systematically moderate any associations. CONCLUSIONS: Despite the high variability in early growth of VLBW infants, the previously described association between slow growth in infancy and poorer cognitive functioning in later life is not reflected in symptoms of depression, ADHD, and other psychiatric problems. This suggests that the development of cognitive and psychiatric problems may have dissimilar critical periods in VLBW infants.